Memantine selectively prevented the induction of dynamic allodynia by blocking Kir2.1 channel and inhibiting the activation of microglia in spinal dorsal horn of mice in spared nerve injury model. (April 2019) - Chen, Yangyang; Shi, Yiqian; Wang, Guoxiang; Li, Yimei; Cheng, Longzhen; Wang, Yun
Background: Memantine is one of the important clinical medications in treating moderate to severe Alzheimer disease. The effect of memantine on preventing or treating punctate allodynia has been thoroughly studied but not on the induction of dynamic allodynia. The aim of this study is to investigate whether memantine could prevent the induction of dynamic allodynia and its underlying spinal mechanisms. Results: (1) In in vivo spared nerve injury pain model, pretreatment with memantine at a lower dose (10 nmol, intrathecal; memantine-10) selectively prevented the induction of dynamic allodynia but not the punctate allodynia. (2) Pretreatment with either MK801-10 (MK801-10 nmol, intrathecal) or higher dose of memantine (30 nmol, intrathecal; memantine-30) prevented the induction of both dynamic and punctate allodynia. (3) Memantine-10 showed significant effect on the inhibition of the spared nerve injury-induced overactivation of microglia in spinal dorsal horn. (4) In contrast, in complete freund′s adjuvant (CFA) model, memantine-10 neither affected the CFA injection-induced activation of microglia in spinal dorsal horn nor the induction of dynamic allodynia. (5) Immunohistological studies showed Kir2.1 channel distributed widely and co-localized with microglia in the spinal dorsal horn of mice. (6) Pretreatment with either minocycline, a microglia inhibitor, or ML133, a Kir2.1 inhibitor, both selectively prevented the overactivation of microglia in spinal dorsal horn and the induction of dynamic allodynia following spared nerve injury. Conclusion: The selective inhibitory effect on the induction of dynamic allodynia in spared nerve injury model by low dose of the memantine (memantine-10) was tightly correlated with the blockade of microglia Kir2.1 channel to suppress the microglia activation.